THE INFLUENCE OF POE LEARNING (PREDICT OBSERVE EXPLAIN) MODEL ON THE UNDERSTANDING OF SCIENCE CONCEPT OF STUDENTS OF SMP NEGERI 32 SEMARANG - Ratna Pujiwati; Endang Susilaningsih (Jurnal Pembelajaran Sains, 2020)
This study aims to determine the influence of the POE (Predict Observe, Explain) learning model on understanding the student's science concept on the material and its application in daily life. This is due to research on using POE learning model to understand the concept has not done much. This type of research isquantitative experimentation with posttest only class experiment control design. The research method began from observation at SMP Negeri 32 Semarang, compiled a research instrument, execute learning with POE model, then analysis of research data and make conclusions. Data analysis results show that the experimental class classical submission was 77 while in the control class of 70. The results expressed the influence of POE learning models to understand the concept. The findings in this study have been the collation between the POE learning model of the understanding of the concept,learning model of the motivation to learn. The conclusion of this study was the influence of POE learning model of the conceptual understanding of 53.13% and the coleration of 43%. The advice of this research is that the use of POE-defecting models that affect students ' understanding can be used as a reference in enhancing the understanding of student concepts.